Experiences of female caregivers who attended a joint HIV prevention programme (Let's talk) with adolescent girls in Soweto - Gunda, Sabastain (My University, 2019)
Introduction Many adolescent girls in South Africa face multiple risk factors to contracting and transmitting HIV. Some of the risk factors include poverty, gender inequity and poor caregiver-adolescent relationships. The steady rise of family-based interventions to prevent HIV infections among adolescent girls has necessitated the need for empirical evidence to gauge their acceptability and feasibility. This study explored the experiences of female caregivers who attended a joint HIV prevention Programme with adolescent girls in Soweto called Let’s Talk. Methods This qualitative cross sectional study used in-depth interviews to gather data from caregivers involved in the Let’s Talk Programme in August 2018. The study was conducted after completion of the programme. Simple random sampling was used to select four Community Based Organisations (CBOs) out of the twelve that implemented the Let’s Talk Programme in Soweto. Twelve caregivers were purposively sampled from the four CBOs on the basis of their proficiency in English. Verbatim audio recording and written notes were used to capture raw data during the interviews. Data analysis was accomplished through manual categorization and coding the data into themes and sub themes. Results Caregivers experienced personal and social challenges that negatively affected their psycho social adjustment, associated with traumatic life experiences like loss of loved ones and sexual abuse. Partly due to lack of parenting skills, caregivers experienced strained relationships with adolescents in their care. Through attending Let’s Talk sessions social support networks available to the caregivers widened, ultimately leading to better caregiver-adolescent relationships. The improved caregiver-adolescent relationships were characterised by better communication, mutual respect and deeper exploration of SRH (including HIV & AIDS) topics. Overall, caregivers shared the perception that Let’s Talk was beneficial. Conclusion Caregivers’ positive perceptions of the Let’s Talk Programme provide empirical evidence of acceptability to participants, effective implementation, and efficacy in facilitating desired outcomes (e.g., behaviour, attitudes and quality of caregiver-adolescent-relationships).
In partial fulfillments of the requirements of the Master of public health degree - social and behaviour change communication at the Wits school of public health June 2019